Dominância fiscal e monetária no Brasil: uma análise do período de 2003 a 2017 - Santos, Daniel Fichman dos (2019)
This paper analyzes the coordination between fiscal policy and monetary policy in the Brazilian economy, in order to investigate possible evidence of a fiscal dominance process, observing the data for the years 2003 to 2017. In this sense, preliminary, it presents, in general lines, the relevant theoretical reference for a reasoned discussion of the theme. Following, the recent evidence for the Brazilian economy on the existence of fiscal and monetary dominance regimes, in which a lack of coordination between both policies, has recently been brought about, has recently provoked the macroeconomic imbalances that make Brazil's interest rate one of the which is intended to finance a sequence of government expenditures that corroborates an increase in the risk of default, currency depreciation and inflation. Next, we present the empirical method of autoregressive vectors (VAR) used to investigate the coordination between fiscal policy and monetary policy, through a causal relationship between the variables primary outcome, net public sector debt, country risk, real exchange rate and inflation. Evidence obtained suggests that the Brazilian economy seems to have moved from an environment of monetary dominance from 2003 to 2010 to an environment of fiscal dominance from 2011 to 2017.